Routine Clinical Practice Treatment Outcomes of Eplerenone in Acute and Chronic Central Serous Chorioretinopathy - Katrin Fasler; Katrin Fasler; Jeanne M. Gunzinger; Jeanne M. Gunzinger; Daniel Barthelmes; Daniel Barthelmes; Daniel Barthelmes; Sandrine A. Zweifel; Sandrine A. Zweifel (Frontiers in Pharmacology, 2021)
Purpose: To evaluate efficacy of eplerenone therapy vs. observation on resolution of subretinal fluid (SRF) in patients with acute and chronic central serous chorioretinopathy (CSCR) in routine clinical practice.Methods: Retrospective comparative case series of eyes diagnosed with CSCR treated with eplerenone or observation. Primary outcome measure was maximum height of SRF at 12 months. Secondary outcome was percentage of eyes with complete resolution of SRF, percentage of eyes with reduction of SRF ≥50%, and best corrected visual acuity (VA) at 12 months. Separate analysis was conducted for eyes with acute and chronic CSCR.Results: Sixty-eight eyes of 60 patients (82% male) were included. Eleven of the 38 eyes with acute CSCR, and seven of the 30 eyes with chronic CSCR, received eplerenone. Subretinal fluid decreased from baseline to 12 months in acute (287 ± 221 to 31 ± 63 µm) and chronic (148 ± 134 to 40 ± 42 µm) CSCR. Kaplan-Meier curves were similar for treated and observed eyes and COX regression analysis did not show a significant difference in SRF resolution in treated vs. observed eyes (p = 0.6 for acute, p = 0.2 for chronic CSCR).Conclusion: This routine clinical practice outcome study did not show evidence of efficacy of eplerenone on resolution of SRF in acute nor chronic CSCR.